TOOLS PROJECT MANAGEMENT OF INNOVATIVE DEVELOPMENT OF ENTERPRISES OF AIRCRAFT INDUSTRY - V. Gafiatullin (Publishing House of the State University of Management, 2016)
In the article the peculiarities of application of tools of project management at the enterprises of the aircraft building complex of the country. Studied the historical aspect of project management as a management practice. Special attention is given to studying of experience of foreign countries have chosen the methodology and tools of project management as a basis of innovative development of enterprises of the aircraft building industry. The analysis highlighted the problems faced by enterprises in the process of implementing the tools of project management. The advantages of implementing the tools of project management, especially for enterprises of the aircraft building industry.